Differences in Physical Activity between Patients with Peripheral Artery Disease and Healthy Subjects - Sumiko Shiba; Akiko Shiba; Atsutoshi Hatada (Journal of Aging Research)
Objectives. Peripheral artery disease (PAD) is a significant prognostic marker of poor long-term survival due to limited physical activity associated with various functional problems, such as intermittent claudication. A physically active lifestyle has the potential to modify peripheral artery risk factors and promote general health. While low daily physical activity levels have been recognized in the population of PAD, the exact level has yet to be quantified due to lack of research. The aim of the present study was to compare physical activity level (PAL) and time spent at activities of different intensity levels between patients with PAD and healthy individuals. The study subjects were 10 patients with PAD and 10 age-matched healthy control subjects. We measured the time spent at light, moderate, or vigorous physical activity using triaxial accelerometer and calculated PAL. Intermittent claudication onset distance and maximum walking distance were defined as the distance walked at which the subject first reported leg pain and the distance at which the subject was unable to continue walking because of leg pain, respectively. Results. Our results showed (i) lower PAL in patients with PAD compared with the controls; (ii) while there was no significant difference in the high-intensity activity between the two groups, the light- and moderate-intensity activities of the PAD group were significantly lower than the controls, the time spent at moderate-intensity activity was approximately 50% less; and (iii) among patients with PAD, low PAL did not correlate directly with intermittent claudication. Conclusions. PAD patients limit the amount of their physical activity, especially light and moderate intensities. Our study highlights the importance of spending more time walking in daily life.